An Attempt in Modeling the Labor Supply Process of Married Women in Tunisia. Issue 7 (2nd October 2016) - Dhouha, HajAli
ABSTRACT: This article is aimed at determining the appropriate model for a married woman's labor supply process in the presence of strategic interaction. We here compare two approaches: a traditional model and a strategic model. We try to estimate the process using Probit and Strategic models and specify, via structural equations, the advantage of the strategic model in the study of strategic data. Using the two models on individual Tunisian data enables us to note that as contrary to the woman expectations in a Probit model, the financial side is not a determining factor in the husband's reaction once his wife gave up her work. This result has been observed only via the strategic model because it takes into account the presence of effect of strategic interaction between a woman's decision and her husband's reaction.